APRS Data Receiver Using Raspberry Pi in LAPAN-A2 Satellite - Sofian Rizal; Sonny Dwi Harsono; Suraduita Mupasanta; Rifki Ardinal (Spektral, 2021)
Lapan-A2 Satellite, also known as LAPAN-ORARI, is the second satellite developed by the Indonesian National Institute of Aeronautics and Space (LAPAN) especially by Satellite Technology Center. This satellite was launched in 2015 which one of the payloads is for amateur radio communication such as VR (Voice Repeater) and APRS (Automatic Packet Reporting System). The APRS is a method of transmitting messages, status and positions using certain range of frequency and often used by Search and Rescue (SAR) team. Due to its function, APRS are not only used for disaster mitigation but also transmit various kind of data such as text message and weather information. In order to receive such information, APRS must be equipped with supporting devices. Formerly, APRS utilize terminal node controller and special hardware to decode its information but those technology is quite expensive. To address that challenge, this paper proposed an alternative way to decode the information send both from satellite APRS and terrestrial APRS by using raspberry Pi to replace those high-cost system.